PROBLEMS OF FORMULATION SKILLS FORMATION IN THE CONTEXT OF THE MODERN APPROACH - O.V. Chebotarenko (Academy of Cognitive and Natural Sciences, 2008)
This Article is devoted to study of the particularities of the process ofthe playing skill finding. The importance of the playing aspect is emphasized in the process of the unscrambling of the music text as symbolic; understanding and entailment semantic pervaded of music language.